Sports monitoring data and video interface using a GUI auto generation Matlab tool - Espinosa, H. G.; James, D. A.; Kelly, S.; Wixted, A. (Procedia Engineering, 2013)
Sport research activities often require graphical user interfaces (GUI) for viewing, merging, tagging and processing of data. More complex processing, like video, requires more complex interfaces but often these GUIs are for short term research use and the investment in creating or purchasing and adapting the GUI is lost. This paper demonstrates an Auto Generation GUI creation tool using Matlab environment. Any GUI is created using a text file that defines all component properties, including the figure, its controls and the callbacks. The auto generation GUI was used in this paper for the creation of a video digitizing interface for monitoring upper arm and forearm rotations of cricket bowlers. This method simplifies the creation and modification of GUIs used in research.